Towards digitalization of Malaysian medical facilities waste management - Mohamed, Nurul Hamizah; Khan, Samir; Jagtap, Sandeep (Cranfield University, 2022)
Medical waste is produced in huge quantities daily, and the increasing amount of it is a worldwide issue that makes managing medical waste more and more crucial. Leakage or improper use of medical waste can be harmful, risking the environment and human lives. The pandemic COVID-19 has challenged current practices with the increasing number of waste and the possibility of transferring the virus from one person to another. In Malaysia, waste management predominantly remains a manual endeavor. where data is usually keyed in either by waste generators, transport contractors, or process occupiers. Digitalization of this setup can be a way to manage waste management effectively as it could be tracked and monitored in real-time. This paper discusses the applicability of exponential technologies, such as Internet of Things and Blockchain, to communicate real-time data to all stakeholders. It presents a framework that can be used to improve the overall waste management process by improving tracking and tractability of waste. Such technology is expected to have an impact across the whole waste management cycle including segregation, storage, transport, and disposal process, and at the same time, help with documentation and administration arrangement.
11th International Conference on Through-life Engineering Services - TESConf 2022, 8-9 November 2022, Cranfield UK
Keywords: medical waste; Malaysia; waste management